Mathematics Curriculum Topic Study : Bridging the Gap Between Standards and Practice. - Keeley, Page D. (SAGE Publications, 2006)
""This book addresses the needs of teachers at every level in their teaching careers, as well as those who support and work with teachers. The processes can be used individually to guide professional learning and teaching, or within almost any professional development structure for facilitating group learning. The CTS process is collegial and scholarly, and truly does bridge the gap between what we know and what we do as educators.""